2015
DOI: 10.1021/acs.chemmater.5b02488
|View full text |Cite
|
Sign up to set email alerts
|

How General is the Conversion Reaction in Mg Battery Cathode: A Case Study of the Magnesiation of α-MnO2

Abstract: α-MnO 2 was previously reported as Mg battery cathode with high discharge capacity but poor cyclability. Surprisingly, the discharge product did not contain any structurally invariant α-Mg x MnO 2 , implying that the magnesiation of α-MnO 2 does not follow the typical intercalation route. In current work we perform a comprehensive analysis about the magnesiation behavior of α-MnO 2 by comparing the reactions following the intercalation and conversion routes. Our results unambiguously demonstrate that the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 46 publications
(168 reference statements)
8
157
2
2
Order By: Relevance
“…[1,14,15] Additionally, most cathodes in modern Li-ion batteries follow an intercalation pathway during electrochemical discharge, while MV battery cathodes have been shown in a number of cases to undergo conversion reactions, [6,[16][17][18][19][20] wherein a reduced transition metal oxide is formed alongside a thermodynamically stable alkaline earth metal oxide, such as MgO. [6,21,22] Because conversion reactions of the type described above are reduction reactions, they occur only upon battery discharge, when the cathode material is being reduced. [6,21,22] Because conversion reactions of the type described above are reduction reactions, they occur only upon battery discharge, when the cathode material is being reduced.…”
Section: Doi: 101002/aenm201800379mentioning
confidence: 99%
“…[1,14,15] Additionally, most cathodes in modern Li-ion batteries follow an intercalation pathway during electrochemical discharge, while MV battery cathodes have been shown in a number of cases to undergo conversion reactions, [6,[16][17][18][19][20] wherein a reduced transition metal oxide is formed alongside a thermodynamically stable alkaline earth metal oxide, such as MgO. [6,21,22] Because conversion reactions of the type described above are reduction reactions, they occur only upon battery discharge, when the cathode material is being reduced. [6,21,22] Because conversion reactions of the type described above are reduction reactions, they occur only upon battery discharge, when the cathode material is being reduced.…”
Section: Doi: 101002/aenm201800379mentioning
confidence: 99%
“…In addition to unveiling complicated mechanism in the magnesiation of rMB cathode (Gautam et al, 2015Ling et al, 2015), computational work helps find suitable cathode candidate for experimental studies. Liu et al (2015) found that among various spinel compounds MnO2 is particularly interesting due to the stability especially at charged state.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The shell was identi- fied as amorphous magnesium oxide mixed with reduced manganese oxide, while the core remains crystalline. 54,55 The thermodynamic driving force for this conversion reaction is attributed to the high stability of MgO.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%